Harmonic Scalpel over Electrocautery, Evaluation of Peroperative Blood Loss in Selective Neck Dissection: A Comparative Study - Agrawal, Manish; Thakur, Sanjeev Kumar; Rahman, Quazi Billur; Agrawal, Atul Kumar; Agrawal, Nancy Bansal (Birat Journal of Health Sciences, 2018)
Introduction: The use of Harmonic Scalpel (HS) over Electrocautery (EC) in neck dissection has become standard of care in recent years. However, both the devices are presently widely used in practice and still serve large number of patients globally according to surgeon's choice and cost effectiveness. Objective: To evaluate the amount of peroperative blood loss in cancer patient undergoing selective neck dissection (Levels I, II and III) with Harmonic Scalpel (HS) and Electrocautery (EC). Methodology: The study was performed in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Biratnagar Hospital PVT LTD and Birat Medical College and Teaching Hospital, Nepal from June 2012 to February 2018. A total of 40 patients, 27 male and 13 female, aged 45 to 70 years diagnosed with oral cavity cancer were included in this prospective study. Two groups were formed, 20 patients in each group based on the surgical instrument used; Harmonic Scalpel (HS) and Electrocautery (EC). Data for age and sex of the patients were collected preoperatively. The surgery was performed under general anesthesia with endotracheal intubation and standard protocol was maintained during surgery. Amount of peroperative blood loss was measured and recorded. Data was processed and analyzed using SPSS and was compiled and test of significance was done using unpaired't' test. Results: The amount of peroperative blood loss was significantly lower in Harmonic Scalpel (HS) group then in Electrocautery (EC) group. Conclusion: Results from this study suggests that the Harmonic Scalpel (HS) is an effective device to reduce peroperative blood loss during selective neck dissection. BJHS 2018;3(2)6: 475-479